2013
DOI: 10.1097/mot.0b013e32835c494f
|View full text |Cite
|
Sign up to set email alerts
|

Machine perfusion in organ transplantation

Abstract: Machine perfusion of solid organs has regained much attention during the last decade. It provides a new promising tool that may allow pretransplant ex-vivo assessment, preservation, repair, and conditioning of grafts. Experimental research and clinical trials testing the administration of MSCs during machine perfusion are warranted to explore the potential benefit and mechanisms of this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(16 citation statements)
references
References 92 publications
0
16
0
Order By: Relevance
“…Several preclinical studies reported the successful delivery of various pharmacological agents, including propofol, hydrogen sulfide, carbon monoxide, nitric oxide, defatting cocktails, and nanoparticles, with the aim to modulate the release of molecules, involved in the IRI-cascade or to provide anti-oxidative protection during machine perfusion [81][82][83][84][85][86][87]. Due to the fact that most of the therapeutic interventions were tested during NMP, only limited data are available with in vivo therapeutics in HMP/HOPE [82,85,86].…”
Section: Allograft Therapies Surgical Interventions and On-pump Drumentioning
confidence: 99%
“…Several preclinical studies reported the successful delivery of various pharmacological agents, including propofol, hydrogen sulfide, carbon monoxide, nitric oxide, defatting cocktails, and nanoparticles, with the aim to modulate the release of molecules, involved in the IRI-cascade or to provide anti-oxidative protection during machine perfusion [81][82][83][84][85][86][87]. Due to the fact that most of the therapeutic interventions were tested during NMP, only limited data are available with in vivo therapeutics in HMP/HOPE [82,85,86].…”
Section: Allograft Therapies Surgical Interventions and On-pump Drumentioning
confidence: 99%
“…The therapeutic application of MSCs has been studied in reducing the IRI after organ transplantation, although their mechanism of action is still unclear [41, 42]. Twelve hour NMP of DCD porcine lungs with intravascular delivery of MSCs has shown increased levels of vascular endothelial growth factor (VEGF) in lungs and reduced levels of interleukin-8 (IL-8), which is a pro-inflammatory cytokine associated with reperfusion injury [43].…”
Section: Machine Perfusion: a Platform For Organ Treatmentmentioning
confidence: 99%
“…Once organs are retrieved from the body, ex vivo treatment especially during machine perfusion becomes possible [6]. Perfusion under physiological conditions providing oxygen and other metabolic substrates facilitates organ function recovery.…”
Section: Ex Vivo Medical Treatmentmentioning
confidence: 99%
“…Extracorporeal membrane oxygenation can even be used in awake, nonintubated patients, bridging the time till they receive a donor organ, and it can also give the patients' own diseased organs time for partial or complete recovery [4,5]. Furthermore, different organ perfusion systems have been developed and implemented in clinical practice in order to maintain the viability of organs ex vivo [6]. …”
Section: Introductionmentioning
confidence: 99%